Electron rich porous extended framework as a heterogeneous catalyst for Diels-Alder reactions - Gole, Bappaditya; Bar, Arun Kumar; Mallick, Arijit; Banerjee, Rahul; Mukherjee, Partha Sarathi (Chemical Communications, 2013)
An electron rich porous metal-organic framework (MOF) has been synthesized, which acts as an effective heterogeneous catalyst for Diels-Alder reactions through encapsulation of the reactants in confined nano-channels of the framework.